Neurodynamic Sciatic Nerve Sliders and Passive Stretching Technique to Reduce Pain and to Increase Hamstring Muscle Flexibility - I Made Dhita Prianthara; Ida Ayu Astiti Suadnyana; I.A Pascha Paramurthi; Ni Luh Anita Chandra Dewi; I Dewa Gde Alit Kamayoga (Universitas Pendidikan Indonesia, 2023)
Short hamstring syndrome is a condition caused by a reduction of the length of hamstring muscles causing muscle tension, muscle strain, and limitations in movement and function. The purpose of this study was to determine the efficacy of the neurodynamic sciatic nerve sliders technique with passive stretching on reducing pain and increasing flexibility of the hamstring muscles in tailors with short hamstring syndrome. This study was an experimental study with pre-test and post-test two group design. The study sample consisted of 22 people given the neurodynamic sciatic nerve sliders technique intervention, for group 1, and passive stretching, for group 2. Pain was measured using a visual analogue scale (VAS), while hamstring muscle flexibility was tested by active knee extension (AKE) measured before and after intervention. Data analysis used paired sample t-test and independent sample t-test. The Paired Sample T-test for pain data of Group 1 obtained p = 0.000 (p 0.05), while the result of Group 2 was p = 0.000 (p 0.05). For the flexibility data of the hamstring muscles, group 1 obtained p = 0.000 (p 0.05) and group 2 obtained p = 0.000 (p 0.05). Independent Samples T-test for pain obtained an average score after treatment of 1.48 ± 1.10 for group 1 and 2.37 ± 0.76 for group 2 with a value of p = 0.039 (p 0.05). For flexibility data, the mean after treatment was 165.00 ± 4.05 for group 1 and 155.00 ± 8.33 for group 2 with a value of p = 0.002 (p 0.05). From these results, neurodynamic sciatic nerve sliders technique and passive stretching can reduce pain and increase hamstring muscle flexibility in tailors with short hamstring syndrome.